Perlindungan Hukum Atas Hak Kompensasi Karyawan PKWT Dalam Pemutusan Hubungan Kerja Secara Sepihak - Sitorus, Stevanus Roy; Simorangkir, Julius Caesar Transon; Malau, Nicholas; Putri, Cantika Widya; Syahrani, Syifa (DPPM Universitas Pelita Bangsa, 2025)
This research discusses the legal protection of pkwt workers regarding compensation rights after unilateral termination of employment using normative juridical methods. This research aims to analyze how compensation payment arrangements are implemented at PT Fuji Prospek Indonesia based on PP No. 35 of 2021. Based on PP no. 35 of 2021, companies are obliged to provide compensation money to employees after the end of the employment relationship, but in fact there is a lack of clarity regarding compensation payments made by PT Fuji Prospek Indonesia, the employee's rights regarding compensation payments are not fulfilled, which is contrary to the provisions of the applicable laws and regulations